A comparative study between felted and triaxial compressed polymer foams on cushion performance. (November 2013) - Ge, Changfeng
A widely used industrial felted foam was compared to a volumetrically heated and compressed foam in this study in terms of cushion performance. The off-the-shelf melamine open cell foam and polyurethane open cell foam were triaxially heated and compressed via an in-house-made device, and energy dissipation was then compared to the felted off-the-shelf open cell melamine and the polyurethane foam. The hysteresis cycle compression test and impact test, in conjunction with a high-speed video camera, were conducted to measure the energy dissipation, G-value, and the Poisson's ratio. Scanning electron microscopy was used to investigate the cellular morphology before and after the felting and volumetric heat and compression. The study showed that both felted foam and triaxial compressed foam demonstrated reasonably well the cushion performance due to the presence of auxetic and microcell structures.